The Role of Legal Culture in Youth Education (Journal of Pedagogical Inventions and Practices, 2022)
The idea that every society is based on its citizens, its family, the role of each citizen in society, the leadership of the rising generation and the crisis begins in the family, nothing can replace the upbringing and education in the family reported.